A SOCIOLOGICAL REVIEW OF ISSUES ON JUVELINE DELINQUENCY. - Ojo, Matthias Olufemi Dada (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi)
Juvenile Justice System is a crucial part in the Criminal Justice Systems of every nation of the world. The proper management of the Juvenile Justice system is a clear indication that such nations are preparing for future generation that will give hope, peace and prosperity. This paper, therefore, examines issues on Juvenile Delinquency and Juvenile Justice System. The paper explains the meanings of Juvenile Delinquency and Juvenile Delinquents. The causes of Juvenile Delinquency are adequately examined rightly from the family level, school and the public. Some sociological theories are employed to explain the theoretical causes of delinquency among the youngsters and their delinquent acts are viewed from masculine and feminine patterns. Issues like Police and the delinquents, Courts and the delinquents and Reformatory Homes and the delinquents are thoroughly explained. Furthermore preventive interventions from the family, school, cognitive -- behaviour and community levels are equally explained. It also examines issues on Nigeria and Juvenile matters. Finally, it recommends that families must be assisted by the government, schools must incorporate teachings on Juvenile Delinquency in their curricula and provide good counseling departments and ready assistance to the less privileged students; the communities in the country should be encourage to provide recreational facilities for the youths and encourage the youths to join social clubs and associations and that the governments should train and equip the Police, Court and Reformatory Homes to handle the Juvenile Justice system in such a way that it will meet the international standards.